Does the frequency and intensity of physical activity in adolescence have an impact on bone? The Tromsø Study, Fit Futures - Christoffersen, Tore; Winther, Anne; Nilsen, Ole-Andreas; Ahmed, Luai Awad; Furberg, Anne-Sofie; Grimnes, Guri; Dennison, Elaine; Emaus, Nina (BMC Sports Science, Medicine and Rehabilitation, 2015)
Background: Optimization of the genetic potential for bone accrual in early life may prevent future fractures. Possible modification factors include lifestyle factors such as nutrition and physical activity. Measured levels of bone mineral density (BMD) and bone mass content (BMC) are indicators of bone strength, and are correlated with fracture risk. This study explored the impact of self-reported physical activity frequencies and intensity on BMD and BMC in Norwegian adolescents. Methods: In 2010–2011 school students in two North-Norwegian municipalities were invited to a health survey, the Fit Future study. 508 girls and 530 boys aged 15–18 years attended. BMD and BMC were measured by dual X-ray absorptiometry. Physical activity and other lifestyle-factors were reported by questionnaires and clinical interviews. Statistical analyses were performed sex stratified, using ANOVA for comparison of means and linear regression models adjusting for factors known to affect bone. Results: Approximately 2/3 of girls and boys reported themselves as physically active outside school hours. Active participants had a significantly higher BMD and BMC at all sites (p < 0.001), except for BMC total body in girls, compared to inactive participants. In multiple linear regression analyses, increased physical activity measured as days a week, categorized into seldom, moderate and highly, was positively associated with BMD (g/cm2 ) at all sites in girls. Girls reporting themselves as highly active had BMD levels 0.093 g/cm2 , 0.090 g/cm2 and 0.046 g/cm2 higher (p < 0.001) than their more seldom active peers at femoral neck, total hip and total body respectively. Corresponding values for boys were 0.125 g/cm2 , 0.133 g/cm2 and 0.66 g/cm2 . BMC measures showed similar trends at femoral neck and total hip. Conclusions: Increased level of physical activity is associated with higher BMD and BMC levels in adolescents. For both sexes high activity frequency seems to be essential, whilst boys reporting quite hard intensity has an ...